The Effect of Electronic Word of Mouth (eWOM) Engagement Toward Purchasing Intention of Beauty and Grooming Products : A Case of LINE Mobile Application in Thailand - Chiyapapharak , Yossaya (Community and Social Development Journal, 2021)
This research investigates the role of user and system characteristics in electronic word of mouth (eWOM) engagement and purchase intention for beauty and grooming products. The research uses a case study of LINE, a social network which has an active community of beauty and grooming product users and interest groups. A survey of Thai LINE users who are members of cosmetic and grooming communities on LINE was conducted. The analysis included descriptive statistics, structural equation modelling (SEM) and moderation analysis. The results showed that user characteristics including user preference, user similarity, user interaction and user concern for others, influenced eWOM engagement, with the strongest effect from user similarity (homophily). System characteristics of perceived ease of use and perceived usefulness were also significant for eWOM engagement, having a stronger effect than user characteristics. eWOM engagement had a significant effect on purchase intention for reviewed products (B = .380). Moderation effects were also observed for age, education level, and income level. The findings are significant because they integrate both system and user factors in eWOM engagement and examine demographic effects for users, which are increasingly important as online use of eWOM spreads in Thailand and it becomes a more frequent source of consumer information.